2013
DOI: 10.1093/brain/awt113
|View full text |Cite
|
Sign up to set email alerts
|

Deleting exon 55 from the nebulin gene induces severe muscle weakness in a mouse model for nemaline myopathy

Abstract: Nebulin--a giant sarcomeric protein--plays a pivotal role in skeletal muscle contractility by specifying thin filament length and function. Although mutations in the gene encoding nebulin (NEB) are a frequent cause of nemaline myopathy, the most common non-dystrophic congenital myopathy, the mechanisms by which mutations in NEB cause muscle weakness remain largely unknown. To better understand these mechanisms, we have generated a mouse model in which Neb exon 55 is deleted (Neb(ΔExon55)) to replicate a founde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 49 publications
9
87
0
Order By: Relevance
“…These studies have revealed that the absence of certain proteins (e.g. nebulin or skeletal alpha-actin), or the presence of mutated amino acids in skeletal alpha-actin and tropomyosin, alter Ca 2+ binding, thin filament conformation and/or the interaction between myosin and actin molecules [86,95,[97][98][99][100][101][102][103][104][105][106][107][108], resulting in reduced force generation at the sarcomere and, ultimately, skeletal muscle weakness.…”
Section: Nemaline Myopathy (Nm)mentioning
confidence: 99%
“…These studies have revealed that the absence of certain proteins (e.g. nebulin or skeletal alpha-actin), or the presence of mutated amino acids in skeletal alpha-actin and tropomyosin, alter Ca 2+ binding, thin filament conformation and/or the interaction between myosin and actin molecules [86,95,[97][98][99][100][101][102][103][104][105][106][107][108], resulting in reduced force generation at the sarcomere and, ultimately, skeletal muscle weakness.…”
Section: Nemaline Myopathy (Nm)mentioning
confidence: 99%
“…The Previous work has shown definitively that mutations in NEB in patients and loss of Neb in mice results in NM, suggesting that decreased NEB in KO mice could contribute to the NM phenotype (1,4,(36)(37)(38). A pervading belief is that NEB acts as a molecular ruler to regulate thin filament lengths based on shortened thin filament lengths seen in Neb-deficient mice (36,37,47). However, more recent studies argue that NEB deficiency contributes directly to a loss in muscle contractility due to dysregulation of actin-myosin crossbridge formation (45,47,48).…”
Section: Generation Of Klhl40mentioning
confidence: 99%
“…A pervading belief is that NEB acts as a molecular ruler to regulate thin filament lengths based on shortened thin filament lengths seen in Neb-deficient mice (36,37,47). However, more recent studies argue that NEB deficiency contributes directly to a loss in muscle contractility due to dysregulation of actin-myosin crossbridge formation (45,47,48). Accordingly, we see over a 50% loss in hind limb strength of P1 KO mice, which have approximately 50% reduction in NEB, without any evidence of sarcomere defects.…”
Section: Generation Of Klhl40mentioning
confidence: 99%
“…This mechanism of action leads to a significantly higher force output at submaximal levels of motor nerve stimulation in animals and humans (Russell et al, 2012;Hansen et al, 2014). Tirasemtiv and its structural analogs have demonstrated efficacy in improving muscle strength in preclinical disease models of neuromuscular origin, including a mouse model of nemaline myopathy (Lee et al, 2013;Ottenheijm et al, 2013), rat model of myasthenia gravis (Russell et al, 2012), and mouse model of amytrophic lateral sclerosis (Hwee et al, 2014). Furthermore, in clinical trials, tirasemtiv improved respiratory function and other measures of skeletal muscle strength and endurance in patients with amytrophic lateral sclerosis (Shefner et al, 2012), myasthenia gravis, and exercise-limiting calf claudication (Bauer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%